Mosquito surveillance of West Nile and Usutu viruses in four territorial units of Slovakia and description of a confirmed autochthonous human case of West Nile fever, 2018 to 2019 - Čabanová, Viktória; Tichá, Elena; Bradbury, Richard Stewart; Zubriková, Dana; Valentová, Daniela; Chovancová, Gabriela; Grešáková, Ľubomíra; Víchová, Bronislava; Šikutová, Silvie; Csank, Tomáš; Hurníková, Zuzana; Miterpáková, Martina; et al. (Euro surveillance, 2021)
BackgroundDespite the known circulation of West Nile virus (WNV) and Usutu virus (USUV) in Slovakia, no formal entomological surveillance programme has been established there thus far.AimTo conduct contemporaneous surveillance of WNV and USUV in different areas of Slovakia and to assess the geographical spread of these viruses through mosquito vectors. The first autochthonous human WNV infection in the country is also described.MethodsMosquitoes were trapped in four Slovak territorial units in 2018 and 2019. Species were characterised morphologically and mosquito pools screened for WNV and USUV by real-time reverse-transcription PCRs. In pools with any of the two viruses detected, presence of pipiens complex group mosquitoes was verified using molecular approaches.ResultsAltogether, 421 pools containing in total 4,508 mosquitoes were screened. Three pools tested positive for WNV and 16 for USUV. USUV was more prevalent than WNV, with a broader spectrum of vectors and was detected over a longer period (June-October vs August for WNV). The main vectors of both viruses were Culex pipiens sensu lato. Importantly, WNV and USUV were identified in a highly urbanised area of Bratislava city, Slovakias' capital city. Moreover, in early September 2019, a patient, who had been bitten by mosquitoes in south-western Slovakia and who had not travelled abroad, was laboratory-confirmed with WNV infection.ConclusionThe entomological survey results and case report increase current understanding of the WNV and USUV situation in Slovakia. They underline the importance of vector surveillance to assess public health risks posed by these viruses.
Keywords: West Nile Fever; Animals; Slovakia; lidé; Slovenská republika; zvířata; Flavivirus; West Nile virus; Culex; virus západního Nilu; západonilská horečka; Culicidae; Humans